A preliminary study of snake bites in Kurunegala, Anuradhapura, and Galle Districts - Perera, U.T.G.; Ekanayake, H.M.T.P.; Chandrasekara, C.M.K.N.K. (University of Colombo, 2017)
South Asia is identified as one of the most vulnerable regions for snake bites in the world. All countries in this region report a significant number of snake bites annually. Sri Lanka is also heavily affected by snake bites. Data from Sri Lanka’s Ministry of Health indicates that poisoning is a main cause of death from snake bites for the period 2006-2015. The main objective of this study is to identify the temporal and demographic differences of individuals with snake bites in the Kurunegala, Anuradhapura and Galle districts. These three districts report high snake bite records in Sri Lanka. Recorded data on snake bites collected from government hospitals in Kurunegala, Anuradhapura, and Galle Districts were selected for the study. MS Excel 2013 and the Statistical Package for Social Sciences were used for data analysis. Percentages and graphs were used to present the information. A total of 1,29,330 patients have been discharged from hospitals after treatment and a total of 287 deaths have been recorded from all three districts during the selected period. The highest number of discharged individuals (55,972) has been reported from hospitals in the Kurunegala District during the study period. It represents 43% of the total recorded live discharges. The highest number of deaths (139) has also been recorded in the Kurunegala District. It represents 48% of the total reported deaths. The Anuradhapura District shows the second highest live discharges and deaths. The Galle District presents the lowest numbers of live discharges and deaths. The results revealed that the vulnerable age group for snake bites is 17 – 49 years in all three districts. This age group included the highest number of live discharged individuals during the period. The recorded live discharges from the hospitals in the Kurunegala District demonstrate a significant decline during the selected period.
Keywords: snake bites, Kurunegala District, Anuradhapura District, Galle District